Factors That Influence Knowledge Of Reproductive Health In Coastal Area Adolescents - Permatasari, Dian; Wardita, Yulia; Damayanti, Cory Nelia; Puspitasari, Dian Ika; Khalifah, Nurul (Chakra Brahmanda Lentera Institute, 2024)
Background: reproduction is an important aspect in health development, especially for adolescents who are in the transition period from childhood to adulthood. Adolescents in coastal areas often face unique challenges that impact their knowledge of reproductive health. These factors can be social, economic, cultural, as well as access to information and health services Methods: This research uses a quantitative approach with a survey method. Data was collected through questionnaires distributed to teenagers in coastal areas. Respondents were randomly selected from several middle and high schools in the area. Data analysis was carried out using statistical software to identify factors that significantly influence adolescent reproductive health knowledge . Results: The results of the study show that factors such as parental education, access to information (0.000), the role of schools (0.037), and peer (0.000) influence significantly influence the level of reproductive health knowledge of adolescents in coastal areas. On the other hand , cultural and economic values of the family also play an important role, but their impact varies more depending on the specific context of each community Conclusion: Knowledge of adolescent reproductive health in coastal areas is influenced by various interrelated factors. Efforts to increase this knowledge must include a holistic approach, involving parental education, increasing access to information, strengthening the role of schools, and addressing cultural norms that hinder it. Intervention programs that focus on teacher training, health campaigns through the media, and improving health facilities in coastal areas can help increase knowledge of adolescent reproductive health.